Pendampingan Penyusunan Laporan Keuangan Pada Mini Market SRC Luthfi di Kelurahan Sidomulyo Barat Pekanbaru Riau - Masril, Masril; Sitinjak, Marnala; Piliang, Arfah; Yusuf, Muhammad (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
MSMEs play an important role in economic growth. There are several problems faced by MSMEs at this time including difficulties in marketing, limited innovation,and technology, as well as limited knowledge about makingfinancial statements. In order to increase interest in the importance of knowledge about financial statements, Thesecommunity service activities are very necessary at this time.The method of devotion is done by giving Lectures, Discussions,and Mentoring.As theresults of this activity, MSME actors already understand how to make financial statements, namely balance sheets and income statements